The effectiveness of using the Hot seating strategy to teach reading texts on Improving reading comprehension and critical thinking skills among sixth-grade students in Jordan - Alamaireh, Eman Abdalfatah (Journal of Educational and Psychological Sciences, 2020)
This research aims to examine the effectiveness of using the hot seat strategy to teach reading texts on Improving reading comprehension and critical thinking skills among sixth-grade students in Jordan. The study was applied on (51) students from forth University school in Amman governorate, distributed randomly into two groups, the experimental group which consisted of (25) students, and a control group which consisted of (26) students. The research used the quasi-experiment design. To achieve the purposes of the study, a test consisted of (24) items was used to measure the reading comprehension skills of the study sample. Watson- Glaser test was also used to measure their critical thinking skills. The study showed that there is a significant effect of teaching by hot seat strategy to improve reading comprehension and critical thinking skills in favor of the experimental group.
Keywords: Hot Seat Strategy; Reading Texts; Reading Comprehension; Critical Thinking